1973
DOI: 10.1111/j.1744-7348.1973.tb01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of aphids reared on cereals and some Gramineae

Abstract: In controlled temperature, light and relative humidity, Metopolophiurn dirhodum and Sitobion avenue multiplied more on young Proctor barley than on Blenda oats, and less on Cappelle wheat. Rhopalosiphum padi increased in number fastest on barley and slowest on oats. More survived, and generation lengths seemed shorter, on barley for M . dirhodum and S. avenue and on wheat for R. pa&.Tests with young cereals outdoors generally agreed with those in controlled conditions. On mature plants, there were more M . dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
2
37
1
Order By: Relevance
“…Dean (1973) tested a single clone of S. avenae from barley on both barley and wheat, and found that the clone tended to perform better on barley than on wheat. Barley clones performed differently in our study when transferred from barley to wheat.…”
Section: S Avenae Clones Specialized?mentioning
confidence: 98%
See 1 more Smart Citation
“…Dean (1973) tested a single clone of S. avenae from barley on both barley and wheat, and found that the clone tended to perform better on barley than on wheat. Barley clones performed differently in our study when transferred from barley to wheat.…”
Section: S Avenae Clones Specialized?mentioning
confidence: 98%
“…However, detailed studies of S. avenae performance on both wheat and barley are rare. Dean (1973) evaluated the development and survival of a single S. avenae clone from barley on barley. The performances of a single S. avenae clone from wheat were determined on both wheat and barley (Watson and Dixon 1984).…”
mentioning
confidence: 99%
“…Several studies compared the development and survival of S. avenae clones on wheat, barley and oat (Adams & Drew, ; Dean, ; Watson & Dixon, ; Gao & Liu, ), but these studies did not characterize the extent of S. avenae specialization to the plant species involved. We hypothesize that divergent selection experienced by S. avenae on different host plants favors the evolution of highly specialized clones for particular hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides abiotic factors like temperature and rainfall, the population differentiation of S. avenae in the areas mentioned earlier may be closely related to the differences in phenology and distribution of cereal crops and wild host plants (Dean 1973), agronomic practices (Gao and Liu 2013), and natural enemy abundance (Entwistle and Dixon 1989). For example, geographic variation in relative host plant abundances may lead to the development of host-adapted populations of S. avenae identiÞed in the studies of De Barro et al (1995), Sunnucks et al (1997), and Gao and Liu (2013).…”
mentioning
confidence: 98%